2021
DOI: 10.1002/mbo3.1236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the skincare product on facial skin microbial structure and biophysical parameters: A pilot study

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…65 Skin dryness can lead to irritation while elevated pH contributes to skin disease and use of appropriate skin care products may restore and preserve skin health. 55 Cleansers with pH close to normal physiologic levels (approximately 5) are a good choice for acne skin to minimize impact on the skin barrier and to favour microbial balance. Conversely, 'poor choices made by an uninformed patient may derail an otherwise ideal therapeutic approach'.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…65 Skin dryness can lead to irritation while elevated pH contributes to skin disease and use of appropriate skin care products may restore and preserve skin health. 55 Cleansers with pH close to normal physiologic levels (approximately 5) are a good choice for acne skin to minimize impact on the skin barrier and to favour microbial balance. Conversely, 'poor choices made by an uninformed patient may derail an otherwise ideal therapeutic approach'.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the authors suggest use that skincare regimen can 'affect the microbial structure of facial skin as well as the biophysical properties'. 55 Cardiello et al and Kong et al also reported that use of skin care products could increase microbial diversity. 56,57 Thermal water is interesting because its physicochemical characteristics may include soluble minerals and trace elements such as selenium or strontium.…”
Section: Maintenance and Protection Of Microbiome: Cleansers And Mois...mentioning
confidence: 98%
See 1 more Smart Citation
“…Kotakeyama et al [7] reported that the skin microbiome of healthy females correlated with the number of pores and the amount of sebum produced. Hwang et al [8] showed that skin hydration and texture correlated with bacterial diversity and changes in the microbial community on facial skin. Furthermore, bacterial diversity was greater in subjects with low hydration than in those with high hydration, and the relative abundance of Cutibacterium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the important role, that a balanced skin microbiome may play in maintaining optimal skin health, appropriate skin care that limits the overgrowth of pathogenic microbial species while reducing oxidative stress and restoring skin homeostasis appears to be crucial in the prevention and therapy of dermatologic conditions [3,14]. Not surprisingly, there is an increasing research interest into natural sources of bio-actives with implicated anti-oxidative and protective properties that act synergistically with other active ingredients of the cosmetic formulation and can strengthen skin barrier integrity and its immune defense system.…”
Section: Introductionmentioning
confidence: 99%